Kebijakan Hukum Rencana Induk Pembangunan Industri dalam Pemanfaatan Potensi Sumber Daya Industri Kehutanan di Indonesia - Esfandiary, Jennifer Kayla; Liu, Fanny; Nabila, Salsa Putri; Rangga, Ferdinandus Kaki; Antoni, Herli (AHKAM, 2023)
This article's objective is to review and discuss the legal guidelines of Indonesia's Master Plan for Industrial Development for the Use of Potential Forestry Industry Resources. The normative methods of legal research that were used to write this article. Forests are important natural resources that provide many ecological, economic and social benefits. Paper is just one of many products and services for which the forestry industry provides raw materials, wood, furniture and building materials. The industry is subject to various laws and regulations governing the management, harvesting and utilization of forest resources. This paper provides an overview of industrial law in the forestry industry, covering key laws and regulations, their impact on the industry, and the legal framework. Industry forest law refers to the legal framework governing the management and utilization of forests for industrial purposes. It includes regulations on logging, reforestation, forest conservation, and the protection of indigenous communities. The aim is to balance the economic benefits of industrial forestry with the need to ensure sustainable forest management and protect the environment.